Photosensitization of nanoparticulate TiO2 using a Re(I)-polypyridyl complex: studies on interfacial electron transfer in the ultrafast time domain - Kar, Prasenjit; Banerjee, Tanmay; Verma, Sandeep; Sen, Anik; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra N. (Physical Chemistry Chemical Physics, 2012)
We have synthesized a new photoactive rhenium(I)-complex having a pendant catechol functionality [Re(CO)3Cl(L)] (1) (L is 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) for studying the dynamics of the interfacial electron transfer between nanoparticulate TiO2 and the photoexcited states of this Re(I)-complex using femtosecond transient absorption spectroscopy. Our steady state absorption studies revealed that complex 1 can bind strongly to TiO2 surfaces through the catechol functionality with the formation of a charge transfer (CT) complex, which has been confirmed by the appearance of a new red-shifted CT band. The longer wavelength absorption band for 1, bound to TiO2 through the proposed catecholate functionality, could also be explained based on the DFT calculations. Dynamics of the interfacial electron transfer between 1 and TiO2 nanoparticles was investigated by studying kinetics at various wavelengths in the visible and near infrared regions. Electron injection into the conduction band of the nanoparticulate TiO2 was confirmed by detection of the conduction band electron in TiO2 (Image ID:c2cp24105f-t1.gif) and the cation radical of the adsorbed dye (1˙+) in real time as monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (<100 fs) electron injection was observed. Back electron transfer dynamics was determined by monitoring the decay kinetics of 1˙+ and Image ID:c2cp24105f-t2.gif.